Performance of multitarget stool DNA testing in African American patients. Issue 19 (7th September 2018) - Cooper, Gregory S.; Markowitz, Sanford D.; Chen, Zhengyi; Tuck, Missy; Willis, Joseph E.; Berger, Barry M.; Brenner, Dean E.; Li, Li
Abstract : BACKGROUND: Multitarget stool DNA (mt‐sDNA) is an approved method for colon cancer screening that is especially relevant for patients who cannot undergo colonoscopy. Although the test performance has been evaluated in a large clinical trial, it was limited to a predominantly white population. Given differences in the epidemiology and biology of colon cancer in African American individuals, the authors sought to compare the performance of mt‐sDNA between racial groups. METHODS: The authors prospectively identified patients aged ≥40 years who were referred for colonoscopy at an academic medical center and 2 satellite facilities. Prior to the colonoscopy, the authors collected stool for mt‐sDNA and fecal immunochemical testing (FIT). They compared the sensitivity, specificity, and receiver operating characteristic curve between African American and white patients for the detection of advanced lesions or any adenoma. RESULTS: A total of 760 patients were included, 34.9% of whom were African American. The prevalence of any adenoma (38.9% for African American patients and 33.9% for white patients) and that for advanced lesions (6.8% and 6.7%, respectively) were similar between groups. The overall sensitivities of mt‐sDNA for the detection of advanced lesions and any adenoma were 43% and 19%, respectively, and the specificities were 91% and 93%, respectively. In general, mt‐sDNA was more sensitive and less specific than FIT. When stratified by race, the sensitivity, specificity, and receiver operating characteristic curve area were similar between African American and white patients for both mt‐sDNA and FIT. CONCLUSIONS: Test performance characteristics of mt‐sDNA were comparable in African American and white patients. Given the lower uptake of colonoscopy in African American individuals, mt‐sDNA may offer a promising screening alternative in this patient population. Abstract : African American individuals have a greater burden of colon cancer with some unique tumor mutations, and are less likely to undergo screening. In a prospective clinical study, the authors report that the test performance characteristics of multitarget stool DNA testing are similar between African American and white patients.